Navigating diverging responsibilities for inclusion in a biobased value chain: the case of Solaris tobacco in South Africa - Eefje De Gelder; Lotte Asveld (Journal of Responsible Innovation)
Companies operating in international, cross-cultural settings encounter challenges in balancing their business roles with responsibilities towards inclusion. This delicate balance is particularly strained within the bioeconomy where uncertainties emerge. This study explores this novelty: how a company engaging in an emerging biobased value chain can fulfil its moral obligations (i.e. responsibility) towards inclusion, aligning with the principles of beneficence (doing good) and non-maleficence (doing no harm). A case study was conducted in the South African Royal Bafokeng Nation where a biobased project, involving tobacco plant cultivation for foremost oil production, was initiated. Our findings suggest that companies in emerging biobased value chains must incorporate local stakeholders' knowledge when establishing their value chains. However, when the implications of beneficence in a specific context are ambiguous, companies should exercise caution in asserting positive responsibilities. Companies should empower local agents to achieve their objectives while refraining from imposing external norms on local contexts.